2007
DOI: 10.2169/internalmedicine.46.6070
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary-Renal Syndrome, Diffuse PulmonaryHemorrhage and Glomerulonephritis, Associatedwith Wegener's Granulomatosis EffectivelyTreated with Early Plasma Exchange Therapy

Abstract: We present a case of a 38-year-old Japanese man with Wegener's granulomatosis complicated with pulmonary-renal syndrome, i.e., diffuse pulmonary hemorrhage and rapidly progressive renal glomerulonephritis. As this is a life-threatening condition, we promptly initiated plasma exchange with intravenous methylprednisolone therapy. Diffuse pulmonary hemorrhage and renal failure were markedly improved. This case merits presentation because there are few clinical studies of the treatment of Wegener's granulomatosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…9 In addition, plasma-exchange therapy may better preserve renal function, with less probability of developing end-stage renal disease. 10 For DAH, previous studies have demonstrated that a combination of remission-induction therapy and plasma-exchange therapy improves pulmonary infiltrates, respiratory function, and mortality rates, 11,12 suggesting that active pulmonary hemorrhage could be an indication of early plasmapheresis. However, there is no consensus in the use of plasma-exchange therapy in pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, plasma-exchange therapy may better preserve renal function, with less probability of developing end-stage renal disease. 10 For DAH, previous studies have demonstrated that a combination of remission-induction therapy and plasma-exchange therapy improves pulmonary infiltrates, respiratory function, and mortality rates, 11,12 suggesting that active pulmonary hemorrhage could be an indication of early plasmapheresis. However, there is no consensus in the use of plasma-exchange therapy in pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors recommend PE therapy in diffuse alveolar hemorrhage 16 but EULAR recommendations for PE do not include extra-renal manifestations. 1 No study on PE in WG has focused on pulmonary involvement alone.…”
Section: Discussionmentioning
confidence: 99%
“…At least 50% of patients with ANCA-associated glomerulonephritis have pulmonary disease. Massive pulmonary hemorrhage affects about 10% of patients with ANCA glomerulonephritis, and is associated with an elevated risk of death (16). Constitutional signs and symptoms, such as fever, myalgias, arthralgias, and malaise, often accompany small-vessel vasculitis.…”
Section: Renal Featuresmentioning
confidence: 99%
“…The duration of induction therapy is 3-6 months (figure 2). In the presence of kidney failure, plasma exchange (plasmapheresis) is often used in addition to pharmacological treatment (16,21,22). Once remission is achieved, treatment is scaled back to maintenance therapy with lower doses of GC, while cyclophosphamide is replaced by a less tox-ic immunosuppressant, such as azathioprine.…”
Section: Induction Therapymentioning
confidence: 99%
See 1 more Smart Citation